Kinerja Struktur Akibat Beban Gempa Dengan Metode Respon Spektrum Dan Time History (Studi Kasus : Hotel Ska Pekanbaru) - Rezky Rendra; Alex Kurniawandy; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Earthquake is a natural disaster that is very difficult to predict, the occurrence is relatively short, but the impact can be very dangerous. Earthquake resistant building design must be implemented in the design of a building. dynamic analysis is necessary to determine structure behavior . In this study, there are two dynamic methods used, they are response spectrum method and time history method. Structures analyzed in this study were Hotel SKA Pekanbaru Building. This study examines the performance of the structure consist of story shear, displacement and story drift when receiving seismic load. spectrum response used is pekanbaru city spectrum response by SNI 1726-2012 while the time history used in this study is the time history of El-centro Earthquake, Mentawai Earthquake Aceh , Earthquake and Padang earthquake. response spectrum method Analysis produce Damage Control (DC) performance level in X direction and Y direction. time history of El-centro earthquake analysis produce Structural Stability (SS) performance level in X direction and Y direction. time history of Mentawai Earthquake analysis produce Immediate Occupancy (IO) performance level in X direction and Y direction. time history of Aceh Earthquake analysis produce Damage Control (DC) performance level in X direction and Y direction . time history of Padang Earthquake analysis produce Structural Stability (SS) performance level in X direction and Y direction.Keyword: Response Spectrum, Time History, Performance Level, Dynamic Analysis